2021
DOI: 10.1007/s10964-021-01416-0
|View full text |Cite
|
Sign up to set email alerts
|

Prospective Associations between Sport Participation and Indices of Mental Health across Adolescence

Abstract: Youth sport offers physical and psychosocial components that may be beneficial for adolescents' mental health, but the prospective directionality between sport participation and mental health has not been clearly established. The current study examined longitudinal associations between sport participation (individual and team sport) and mental health indices (depressive symptoms, anxiety symptoms, emotional symptoms, hyperactivity symptoms, conduct problems, peer problems, and prosocial behavior) across adoles… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
41
1

Year Published

2021
2021
2024
2024

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 47 publications
(45 citation statements)
references
References 47 publications
3
41
1
Order By: Relevance
“…Participation in sport may promote child and adolescent mental health because of the many fruitful opportunities to build social relationships and friendships, which can help foster a sense of belongingness within the athletic context [ 13 ]. Social interactions and feelings of relatedness with others are inherent aspects of team sport participation.…”
Section: Introductionmentioning
confidence: 99%
“…Participation in sport may promote child and adolescent mental health because of the many fruitful opportunities to build social relationships and friendships, which can help foster a sense of belongingness within the athletic context [ 13 ]. Social interactions and feelings of relatedness with others are inherent aspects of team sport participation.…”
Section: Introductionmentioning
confidence: 99%
“…Specifically, the Iowa Bone Development Study indicated that sports participation could predict later sufficient physical activity ( 6 ). Several recently published research articles using longitudinal design have demonstrated a potentially negative association between greater sports participation and fewer symptoms of depression and anxiety in adolescents ( 1 , 7 , 8 ). Vella et al ( 9 ) concluded that sports participation was positively correlated with the adherence to screen time and physical activity guidelines as well as fruit and vegetable consumption guidelines.…”
Section: Introductionmentioning
confidence: 99%
“…The importance of especially leisure-time PA in the relationship between PA and mental health is well-documented (48)(49)(50)(51) and may be explained, for example, by voluntary nature, own preferences, enjoyment and possibilities for social interactions (7,52). A number of other previous studies using self-reported PA data (53)(54)(55) have shown that activities that are more likely to be practiced in group, are strongly associated with lower depressive symptoms and better mental well-being, especially in men (55).…”
Section: Discussionmentioning
confidence: 99%